(untitled) (Rudarsko-geološko-naftni zbornik, 2016)
This paper establishes hydrogeological and hydrogeochemical characteristics of a wider area of the regional well field Eastern Slavonia - Sikirevci. The research was conducted based on data gathered from the area of the Federation of Bosnia and Herzegovina and the Republic of Croatia. The aquifer Velika Kopanica is situated at the territory of the Republic of Croatia in the triangular region formed between Kopanica, Gundinci and Kruševica. The River Sava partially flows through it and the aquifer extends beneath the river to the territory of the Federation of Bosnia and Herzegovina from Donji Svilaj in the West to Domaljevac in the East where its yield is the highest. The thickness of the aquifer decreases towards the water body Odžak. It was determined that the groundwater which is extracted from wells of the wider area of the regional well field contains iron, manganese, natural ammonia and arsenic in values exceeding the maximum allowable concentration for drinking water. The increased values of these parameters are a result of mineral composition and reductive conditions in the aquifer environment. By means of a multivariate statistic cluster analysis, an overview of groups of elements is provided based on geochemical affinity and/or origin.